The Effectiveness of the Direct Method in Improving English Speaking among Secondary School Students - Rizky Putra; Desty Febria; Maya Marsevani (Journal of English Education Program (JEEP), 2026)
Despite the widespread implementation of the Direct Method in EFL classrooms, empirical evidence examining students’ perceptions of its role in developing speaking skills remains limited, particularly in small-scale instructional contexts. This study aims to explore EFL students’ perceptions of the Direct Method in enhancing their speaking ability. This study employed a qualitative descriptive research design to explore students’ perceptions of the use of the Direct Method in developing speaking skills. Semi-structured interviews and classroom observations were used as data collection instruments to allow methodological triangulation and enhance the credibility of the findings. This study involved 26 students from  grade VII and 1 English teacher. Researchers have been conducted the observation three times and the interview on the following week. The findings indicate that the Direct Method contributed to increased learner confidence, improved vocabulary recall, and greater classroom engagement; however, students also reported challenges related to pronunciation accuracy and spontaneous sentence production.